A Study on Perception of Youngsters Towards Entrepreneurship - Ramkumar, Gowtham (AMC Indian Journal of Entrepreneurship, 2018)
Unemployment has again become a serious problem in the country. Large number of undergraduates and postgraduates are passing out every day. There is a large gap between demand and supply of skills of human resources in the country. To bridge this gap various skill development programs have been introduced by the government and initiatives are also being taken by educational institutions to develop skill level of the students. On the other hand, the government is encouraging youngsters to start new business and is willing to support them. This study focuses on the perception of youngsters towards entrepreneurship. The study finds out the factors affecting the perception of youngsters towards entrepreneurship. Finally, this study provides a meaningful conclusion and provides scope for further research in this area.